2022
DOI: 10.3390/ijms23126867
|View full text |Cite
|
Sign up to set email alerts
|

IgG from Adult Atopic Dermatitis (AD) Patients Induces Thymic IL-22 Production and CLA Expression on CD4+ T Cells: Possible Epigenetic Implications Mediated by miRNA

Abstract: Atopic dermatitis (AD) is a common relapsing inflammatory skin disorder characterized by immune-mediated inflammation and epidermal barrier dysfunction. The pathogenesis of AD is multifactorial and has not been fully elucidated to date. This study aimed to evaluate whether serum IgG from adult AD patients could modulate the thymic maturation of IL-22-producing T cells and CLA+ T cells of non-atopic infants. Given that miRNAs regulate immune response genes, we evaluated whether miRNA expression is also altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…More recently, it was demonstrated that purified IgG from AD individuals could induce overexpression of cutaneous lymphocyte-associated antigen (CLA) on thymic CD4+ T cells since its immature DP stage in vitro , an effect that was not observed on CD8+ T cells, where an opposite effect was revealed [ 28 ]. This observation was relevant because CLA-expressing CD4+ T cells can be considered a peripheral biomarker of AD [ 29 ].…”
Section: Experimental Evidence On the Immune Tolerance Induced By Iggmentioning
confidence: 99%
“…More recently, it was demonstrated that purified IgG from AD individuals could induce overexpression of cutaneous lymphocyte-associated antigen (CLA) on thymic CD4+ T cells since its immature DP stage in vitro , an effect that was not observed on CD8+ T cells, where an opposite effect was revealed [ 28 ]. This observation was relevant because CLA-expressing CD4+ T cells can be considered a peripheral biomarker of AD [ 29 ].…”
Section: Experimental Evidence On the Immune Tolerance Induced By Iggmentioning
confidence: 99%
“…In this theory, direct binding of idiotype of polyvalent IgG to the TCRs or unidentified antigens on the surface of CD4 + cells can induce differentiation of Treg cells from naive T cells or activate pre-existing Treg cells to secrete IL-10 ( Figure 1C ). The direct interaction between polyvalent IgG and antigens on the cell membrane of CD4 + thymic T cells induced cytokine production from CD4 + thymic T cells ( 53 ). However, this study did not evaluate the activation of Treg cells by direct binding of polyvalent IgG to antigens on the cell membrane of T cells.…”
Section: Four Hypothetical Models For the Mechanism Underlying Polyva...mentioning
confidence: 99%
“…According to some authors, the natural history of AD suggests that males predominate in childhood and females after puberty [ 6 ]. Studies in Europe have suggested an increase in the incidence and prevalence of AD in the 21st century compared to the 20th century [ 7 , 8 ], possibly due to various factors such as genetic and epigenetic factors, impaired skin barrier integrity, autoimmunity, viral infections, gut microbiome composition, dietary habits, and lifestyle factors [ 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Recent research has shown functional links between genetic variants in the IL-17 promoter, the gut microbiome, and AD [ 17 ].…”
Section: Introductionmentioning
confidence: 99%